2020
DOI: 10.5811/cpcem.2020.5.48318
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Disposition of Symptomatic Probable COVID-19

Abstract: Introduction: The novel coronavirus disease 2019 (COVID-19) presents a challenge for healthcare providers in terms of diagnosis, management, and triage of cases requiring admission. Case Report: A 47-year-old male with symptoms suspicious for COVID-19, pulse oximetry of 93% on room air, and multifocal pneumonia was risk stratified and safely discharged from the emergency department (ED) despite having moderate risk of progression to acute respiratory distress syndrome. He had resolution of his symptoms verif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Previous studies have reported that monitoring of outpatients with COVID-19 is effective in identifying patients with alarming symptomatology. Remote follow-up of ambulatory patients has been evaluated during the acute phase of illness, both in adult ( 3 ) and pediatric patients ( 4 ) with mild SARS-CoV-2 infection after being discharged from the hospital and in some patients with pneumonia even with moderate risk of progression to acute respiratory distress ( 12 ), and remote monitoring has been associated with a reduction in hospital readmission ( 13 ). However, a systematic review of remote monitoring concluded that the real effectiveness of the different interventions could not be determined reliably.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that monitoring of outpatients with COVID-19 is effective in identifying patients with alarming symptomatology. Remote follow-up of ambulatory patients has been evaluated during the acute phase of illness, both in adult ( 3 ) and pediatric patients ( 4 ) with mild SARS-CoV-2 infection after being discharged from the hospital and in some patients with pneumonia even with moderate risk of progression to acute respiratory distress ( 12 ), and remote monitoring has been associated with a reduction in hospital readmission ( 13 ). However, a systematic review of remote monitoring concluded that the real effectiveness of the different interventions could not be determined reliably.…”
Section: Discussionmentioning
confidence: 99%